Languaging in Multimodal Digital Interaction: An Enactive Exploration of Emoji Metaphors and Meanings - Agnese Sampietro (Signifiances (Signifying))
Emojis, small pictographic characters commonly used in electronic messages, have become a global phenomenon. This study utilizes key enactive concepts to demonstrate how emojis reflect the ongoing interplay between technology, language, and culture. A central theme of the analysis is the role of metaphors in justifying the design, use, and interpretation of emojis, illustrating how these symbols originate, evolve, and adapt to the contextual nuances of our environment. The ultimate goal of this study is to enhance our understanding of the evolving meanings of emojis, emphasizing their dynamic nature, and enriching our understanding of their role and interpretation in contemporary human expression and interaction. In this context, emojis emerge as cultural artifacts that are both shaped by and continually shape how we communicate and interact in the digital age.